The impacts of crisis on state-level tourism demand in Malaysia - Ooi , Chai Aun; Hooy , Chee Wooi; Mat Som, Ahmad Puad (2013)
This paper focuses on the changes of state-level tourism demand in Malaysia over three crisis events in Asia, i.e. 2003 SARS outbreak, 2004 Indonesian tsunami and 2005 Bali bombing. Among the 13 states in Malaysia, tourism demand in every state is varied. We find that the four highest demanding states, namely Selangor, Penang, Malacca and Pahang, together with Perak and Terengganu are significantly affected by the crises, with only Penang has positive relationship, but negative relationships are found for the others. We further find that the negative impacts of 2005 Bali bombings towards Malaysian tourism demand are not less than the other two crises although Malaysia is not implicated into the crisis. This may suggest that spillover effect of tourism crisis is possible.